Potensi Naskah-Naskah Islam Minangkabau untuk Industri Kreatif sebagai Pendukung Wisata Religi Ziarah di Sumatera Barat - Pramono Pramono (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
The manuscripts of Minangkabau are mostly the collection of surau tarekat scattered in various places in West Sumatera. Some of the surau are always crowded visited by the congregation. Based on that phenomenon, this research is designed to discover and explore the potency of Minangkabau manuscripts that can be developed as a creative industry. Through these manuscripts are expected to provide support for the development of religious pilgrimage tour in West Sumatera which has not been managed properly and maximally until now. The method of the research applied is qualitative research method with three approaches, namely philology, codicology and creative industry. The data were collected through five stages, namely observation, recording and collection of manuscripts, literature studies, interviews and textual criticism. The technique applied in analyzing the data is based on the phenomenology approach to obtain a comprehensive understanding of the subject of the research. This study concludes that through the organization of the manuscripts containing the biographical content of tarekat scholars and their thought can turn the creative industries on, particularly the publishing sector. In addition, through illumination engineering (decoration in the script) can be developed into batik motifs. The publication of the selected manuscript text and the production of illuminated batik manuscripts can be a unique souvenir of religious pilgrimage tours in surau tarekat in West Sumatera.